2013
DOI: 10.1007/978-3-642-40498-6_25
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Elderly User Behavior on Mobile Multi-touch Devices

Abstract: Abstract. Smartphones and tablet devices have been rapidly proliferating, and multi-touch interaction, powerful processors and rich array of sensors make these devices an attractive service platform for older users. While there is an increasing number of work investigating the issues that elderly users experience through their interaction with mobile devices, most have focused either on evaluation of low-level interaction characteristics or on qualitative survey. Therefore, we conducted a user study with 21 el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 20 publications
(26 reference statements)
0
25
1
5
Order By: Relevance
“…This could also be related with the layer types of the resistive touch-screen technology. Harada et al's [46] study also support dry-finger and users' frustrations with unresponsive taps.…”
Section: Physical Challengesmentioning
confidence: 77%
See 1 more Smart Citation
“…This could also be related with the layer types of the resistive touch-screen technology. Harada et al's [46] study also support dry-finger and users' frustrations with unresponsive taps.…”
Section: Physical Challengesmentioning
confidence: 77%
“…Evidence already reveals that there are a number of challenges to be aware of when digital technologies are used by older adults including physical issues such as decline in manual dexterity and eyesight and decreasing cognitive capabilities, frustration, the need for specific training, age, gender, dry finger skin, and age-related cognitive motor skills [2,[18][19][20][21][22], all factors likely to affect the performance of RT and IIV RT tests using a touch screen platform and thus their clinical validity, usefulness, and robustness. Furthermore, RT research has revealed many participant and methodology-related factors capable of significantly affecting RT study outcome including: the test item, the environment, response requirements, participant and tester, feedback, concurrent disease, medication, abnormal visual and attention-related processes, caffeine, depression, personality, and gender [11][12][13][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…There are sound biophysical reasons why older individuals and individuals with poorer health would have more difficulty with technological input devices: worsening eyesight, less motor control, and decreased strength (Taveira & Choi, 2009; Caprani et al, 2012). Touch interfaces sometimes use specific gestures for zoom, selection, and panning, and the precision required may challenge older individuals (Harada et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Harada et al (2013) [7] have observed that novice users make shorter gestures for panning or scrolling tasks.…”
Section: Related Workmentioning
confidence: 99%